2022
DOI: 10.1097/cm9.0000000000001985
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity patterns and association with mortality in 0.5 million Chinese adults

Abstract: Background: Few studies have assessed the relationship between multimorbidity patterns and mortality risk in the Chinese population. We aimed to identify multimorbidity patterns and examined the associations of multimorbidity patterns and the number of chronic diseases with the risk of mortality among Chinese middle-aged and older adults. Methods: We used data from the China Kadoorie Biobank and included 512,723 participants aged 30 to 79 years. Multimorbidity was defined as the presence of two or more of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 35 publications
2
38
2
Order By: Relevance
“…Moreover, as an essential risk factor for CHD, DM can exacerbate the progression of atherosclerosis, resulting in poor clinical outcomes [ 3 , 4 ]. A 2022 study in China by Junning Fan et al on 500,000 Chinese has shown that diseases, including CHD and DM, greatly portend the risk of mortality among Chinese adults [ 5 ]. The management of glucose metabolism in patients with CHD is therefore particularly important.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as an essential risk factor for CHD, DM can exacerbate the progression of atherosclerosis, resulting in poor clinical outcomes [ 3 , 4 ]. A 2022 study in China by Junning Fan et al on 500,000 Chinese has shown that diseases, including CHD and DM, greatly portend the risk of mortality among Chinese adults [ 5 ]. The management of glucose metabolism in patients with CHD is therefore particularly important.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic kidney disease (CKD) is a major public health problem with substantial comorbidities and disease burden. The statistics from the Global Burden of Disease Study 2017 reveal that approximately one-tenth of the world's population was affected by CKD, and that it ranked as the 12th leading cause of death globally, causing 35.8 million disability-adjusted life years in 2017 [1,2] …”
Section: Introductionmentioning
confidence: 99%
“…In a cohort of 0.5 million Chinese adults, the multimorbidity rate was 15.8%. The highest mortality is caused by cardiometabolic multimorbidity, and any combination of cardiometabolic Frontiers in Genetics frontiersin.org multimorbidity has a multiplicative mortality risk (Fan et al, 2022). The gut-heart axis has been proposed on the basis of accumulating evidence that gut dysbiosis plays a crucial part in the progression of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%